nCOVID-19: Its diagnosis, possible preventive measures, therapeutic interventions and management - Mrinal Kanti Poddar; Apala Chakraborty (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Novel coronavirus (nCOVID-19) is a current global threat causing severe infections to millions of people throughout the world. WHO has reported in their case-based surveillance that the aged and male populations are most vulnerable to this recent coronavirus infection. This disease-causing virus, named as SARS-CoV-2, is a respiratory coronavirus that probably originated from the bat with a substantially different genetic makeup concerning the other known coronaviruses. Structurally SARS-CoV-2 is a diverse single-stranded RNA virus having spike (S) glycoprotein in its envelop that is associated with the transmission of the virus by binding with the host target receptor. The principal target site of nCOVID-19 is angiotensin-converting enzyme 2 (ACE2) in the host receptor. The expression of ACE2 target site varies according to the genetic susceptibility and ABO blood group locus causing variation in the severity of the infection. The virus usually affects the inflammatory pathways, responsible for white blood cell activation and clot formation after interacting with pathogen pattern recognition receptors. The major pathological symptoms of severe nCOVID-19 are mild to severe respiratory and bowel syndromes. Prevention of infections has been achieved by social distancing depending on the concept of aerosolized/droplet transmission of virus and by maintaining personal hygiene. Remedies like ayurvedic, homeopathic, micronutrients such as vitamins and minerals along with regular physical exercises like yoga and meditation are also found to be helpful in disease prevention. The treatments that have been applied so far with some positive responses are antimalarial chloroquine and hydroxychloroquine, antivirals, plasma therapy, steroids, omega-3-fatty acid derivatives, vitamin C infusion, etc. Some global healthcare bodies are also in action for the development of vaccines therapy against nCOVID-19. Apart from the infection control, some other associated issues like long term social distancing, constant stress, anxiety, change in lifestyle are affecting adversely the aged populations and also the other part of the society. There is no doubt that government bodies from various countries throughout the world are taking extreme measures to control and mitigate the pandemic, but this untoward situation is still far from the control of human races and supposes to take more time and further scientific interventions and management are needed to be continued.